A study to evaluate the relationship between diabetes mellitus and cognitive dysfunction - Rakesh Kumar Patel; Karan Saran Kapur; Sardar Eske (Asian Journal of Medical Sciences, 2022)
Background: Diabetes mellitus (DM) is the most common endocrine disorder. It leads to slow progressive end-organ damage (both microvascular and macrovascular). The cognitive dysfunction is a less known and less addressed complication of DM.